(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2018)
In 1903, a small group of women led by Emmeline Pankhurst established the Women`s Social and Political Union, in Manchester. This organization was distinguishing from the rest of the suffrage movement because of the radical strategies and methods of struggle in order to conquest their goal. The very quick response was the symbolic violence toward them and, soon, the physical punishment to these women who threatened the whole social order when they disavowed the dictate of their natural sweetness and peacefulness. They used direct action methods - like West End windows-breaking campaign by throwing stones, artwork outrages, setting fire to letters in boxes and other arsons, interruptions to liberal Party meetings – which constituted a challenge to their supposed female nature were follow by fines, arrests, knocks and mistreatments. This article is about the confinement and punishment experiences through the female voices in order to understand how the repressive measures were received by them, as they capitalized them as a strong political propaganda in their favor.